2006
DOI: 10.1021/jp065679t
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Intermolecular Structure and Dynamics in Supercritical Carbon Dioxide with Pressure:  An ab Initio Molecular Dynamics Study

Abstract: The effect of pressure on supercritical carbon dioxide (scCO2) has been characterized by using Car-Parrinello molecular dynamics simulations. Structural and dynamical properties along an isotherm of 318.15 K and at pressures ranging from 190 to 5000 bar have been obtained. Intermolecular pair correlation functions and three-dimensional atomic probability density map calculations indicate that the local environment of a central CO2 molecule becomes more structured with increasing pressure. The closest neighbors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
70
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 43 publications
19
70
0
Order By: Relevance
“…Theoretical studies of simple quadrupolar liquids [45,46] have shown that this arrangement originates from the electric quadrupole-quadrupole (EQQ) interactions, since the larger the quadrupole is, the higher is the probability to find T-shape configurations. Our findings agree very well with previous works based on neutron diffraction data [25] or ab initio calculations [41] at similar densities (14.9-19.17 molecules/nm 3 ). The fact that the same molecular configurations are obtained with ab initio calculations and with the classical potential used in the present paper gives further credit in the ability of the latter to describe the structure of liquid CO 2 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Theoretical studies of simple quadrupolar liquids [45,46] have shown that this arrangement originates from the electric quadrupole-quadrupole (EQQ) interactions, since the larger the quadrupole is, the higher is the probability to find T-shape configurations. Our findings agree very well with previous works based on neutron diffraction data [25] or ab initio calculations [41] at similar densities (14.9-19.17 molecules/nm 3 ). The fact that the same molecular configurations are obtained with ab initio calculations and with the classical potential used in the present paper gives further credit in the ability of the latter to describe the structure of liquid CO 2 .…”
Section: Discussionsupporting
confidence: 93%
“…[41], this configuration of molecules in the first shell is remarkably similar to that found in the P a3 crystal structure of phase I. In the latter indeed, each CO 2 molecule has 12 first neighbors at the same C-C distance (r = 0.398 nm at the melting point 0.57 GPa, 300 K [47]), six of which are in the equatorial plane and the other six are around the poles [see Fig.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…CO 2 molecule in supercritical phase shows unique characteristics of liquid-like density and gas-like diffusivity in addition to its nontoxic behaviour, as observed in neutron diffraction experiments. [14][15][16] It has been observed in some earlier studies that, due to close proximity of the monomers in these dense phases, the CO 2 molecules no longer remain linear, [17][18][19][20] giving rise to instantaneous dipole moment. Thus we believe, which can be understood in the light of their linear and nonlinear optical response functions.…”
Section: Introductionmentioning
confidence: 91%
“…In the top panel of Figure 4 18 O). The presence of that impurity, and of its complex with DME, is confirmed by very weak bands in the 3490-3460 cm À1 region.…”
Section: à5mentioning
confidence: 99%